Malignant hypercalcemia associated with ovarian dysgerminoma: a case report (BIRDEM Medical Journal, 2022)
Hypercalcemia is a well-recognized and potentially dangerous paraneoplastic manifestation of malignancy; furthermore, it is an important cancer related medical emergency. It has been endured in association with a number of malignancies; however, it is an unusual presentation of ovarian cancer like dysgerminoma. This neoplasm along with refractory hypercalcemia, which usually affects the young women, is a sign of advanced disease and indicates poor prognosis. In this report, we present a case of 31-year-old female, who presented with features of hypercalcemia which was associate with ovarian dysgerminoma.BIRDEM Med J 2022; 12(2): 158-160